Os lagares cavados na rocha do castelo de Castorigo - Pegarinhos (Alijó) - Almeida, Carlos A. Brochado de; Pinto, Paulo J. Costa; Almeida, Pedro Miguel D. Brochado de (Douro : Estudos & Documentos, 2022)
.